Bioluminescence screening in vitro (Bio-Siv) assays for high-volume antimycobacterial drug discovery. - Arain, T M (1996)
Bioluminescence-based assays to indicate antimicrobial susceptibility have been developed and validated for recombinant strains of Mycobacterium tuberculosis, Mycobacterium bovis BCG, Mycobacterium avium, and Mycobacterium intracellulare expressing an integrated eukaryotic luciferase gene. MICs determined with these bioluminescence assays for several antimycobacterial agents, including isoniazid, ethambutol, rifampin, amikacin, streptomycin, ciprofloxacin, and clarithromycin, compared favorably with traditional BACTEC methods and visual estimations of the inhibitory end point. Assay methodology has been optimized for the analysis of large numbers of novel compounds and is simple, inexpensive, and labor efficient. The availability of these four recombinant mycobacteria has permitted a strategy for drug discovery employing the nonpathogenic BCG strain for mass screening purposes with subsequent confirmation of activity against the pathogenic mycobacteria. Furthermore, evidence suggests that the BCG-based screen may allow the direct identification of bactericidal agents.